Going public '04 : Mappe, confini, nuove geografie = Maps, confines and new geographies. - Exhibition. Going public '04 : Mappe, confini, nuove geografie. Modena. Provincia di Modena. 2004-10-09. 2004-12-09; AES Group; Boullata, Kamal; Brizzi, Marco; Chevrier, Jean-François; Farinelli, Franco; Hanru, Hou; Khan, Hassan; Mulholland, Elizabeth; Obrist, Hans Ulrich; Stratis, Socrates; Tzirtzilakis, Yorgos; et al. (Cinisello Balsamo (Milano) Modena : MAST (Museo d'Arte Sociale e Territoriale) Provincia di Modena Silvana Editoriale Cinisello Balsamo (Milano), 2004)
AES ; A 12 ; Akerman, Chantal ; Collettivo Zapruder ; Cnaani, Ofri ; Gibilterra Project (f/p+f/z) ; Hari, Hariklia ; Hirschhorn, Thomas ; Khan, Hassan ; Landau, Sigalit ; Shibli, Ahlam ; Torolab ; Xagoraris, Zaphos
biog. kunstenaars & auteurs p. 145-156
Engels
Italiaans
boek